(untitled) (Indian Journal of Child Health, 2021)
Background: The renal tubules maintain homeostasis through an array of proteins coded by multiple genes, which directly or indirectly transport water and solutes in the tubules. Malfunction of these transport proteins leads to inherited tubulopathies. Objective: The objective of the study was to analyze the clinical utility of next-generation sequencing (NGS) in the diagnosis and management of children with tubulopathies. Materials and Methods: This retrospective study was conducted in a tertiary care nephrology center in West India between September 2016 and September 2020. All children ?18 years with suspected inherited tubulopathy, where an NGS was sent, were included. Clinical exome sequencing (CES) covering 6670 genes was done in 14 children. CES included 73 tubulopathy genes. The test result was interpreted as per American College of Medical Genetics classification: No pathogenic variant, variant of unknown significance (VUS), and likely pathogenic and pathogenic variant. Results: The median age (IQR) of the cohort at the onset of disease was 18 months (4–65). History of consanguinity was present in 2 children (14.2%). Five children (35.7%) had Fanconi syndrome, two had distal renal tubular acidosis (d-RTA), two had Bartter/Gitelman syndrome, two had rickets, two had nephrocalcinosis, and one had low-molecular-weight proteinuria. Nine children (64%) had pathogenic variants detected in eight genes: ATP6V0A4, CTNS1, FAH1, PHEX, SLC12A1, SLC4A1, SLCA2, and CLDN 16. Five (35.7%) were novel variants. Two children had three VUS in FAT1, EYA1, and KCNJ1 gene. Three children (21.4%) had no genetic variant. Bartter syndrome type 1 and d-RTA were the most common genetic diagnoses with two patients each. Other diagnoses were tyrosinemia type 1, nephropathic cystinosis, Fanconi Bickel syndrome, X-linked hypophosphatemic rickets, and familial hypomagnesemia, hypercalciuria, and nephrocalcinosis in one each. Conclusion: The yield of NGS in children with tubulopathy was remarkably high. NGS was useful in the diagnosis and management in these children.